DO WE NEED P2P BETWEEN BANK THIRD PARTY FUNDS AND BANK CREDIT? - Cliff Kohardinata; Luky Patricia Widianingsih (Research In Management and Accounting (RIMA), 2023)
The main objective of this study is to obtain empirical evidence on the role of peer-to-peer (P2P) lending mediation in bridging the relationship between banking third party funds and bank credit in provinces with fewer branch offices or limited banking services. The test used is path analysis involving 33 provinces in Indonesia in the period from January to July 2022. The main results of this study show that third party funds in provinces with fewer banking branch offices have no effect on bank credit, but P2P lending can mediate the relationship between banking third party funds and bank credit in provinces with fewer banking branch offices. The additional results of this study indicate that banking third party funds in provinces with a greater number of bank branch offices have a positive effect on bank credit. The novelty of this research is that the researchers introduced the P2P lending mediating variable based on financial technology (FinTech) as a solution for provinces with limited access and exposure to banking to be able to bridge the distribution of third-party funds to debtors, thereby increase financial inclusion.